Calculus 1

Find the derivative of y with respect to x. y=(x^6/6)(lnx)-(x^6/36)

So far this is what I've gotten:

y=(x^6/6)(lnx)-(x^6/36)
y=(1/6)x^6(lnx)-(1/36)x^6
y'=(1/6)x^5(1/x)+lnx(x^5)-(1/6)x^5

What do I do now?

  1. 👍 0
  2. 👎 0
  3. 👁 158
asked by Alex
  1. You forgot various parts.

    If y = uv, y' = u'v + uv'
    If y = u^n, y' = nu^(n-1) u'

    So,

    y' = [1/6 * 6x^5 * lnx] + [1/6 x^6 * 1/x] - 1/36 * 6x^5

    or, you can factor stuff out first:

    y = 1/6 x^6 (lnx - 1/6)
    y' = [1/6 * 6x^5](lnx - 1/6) + 1/6 x^6 * (1/x)

    Either way you can massage things till you get

    x^5 lnx

    1. 👍 0
    2. 👎 0
    posted by Steve

Respond to this Question

First Name

Your Response

Similar Questions

  1. Calculus

    Find the derivative of y with respect to x. y= [(x^5)/5]lnx-[(x^5)/25] How would I go about doing this? Should I use the product rule to separate (x^5)/5]lnx ?

    asked by Natalie on September 4, 2011
  2. calculus

    (a) find the intervals on which f is incrs or decrs. (b) find the local min/max values of f. (c) find the intervals of concavity and the inflection points. f(x)=(lnx)/sqrtx I took the derivative and got 2-lnx/2x^3/2 take the

    asked by Riley on April 6, 2009
  3. Calculus

    Find the derivative of y with respect to x. y= (lnx)/(3+4lnx) Should I start by using the quotient rule?

    asked by Natalie on September 4, 2011
  4. CALCULUS HELP

    Find the second derivative for the function 5x^3+60x^2-36x-41 and solve the equation F(X)=0 i got to the second derivative but what do we do next to be able to get one of these answers.. F(x) = 5x3+60x2−36x−41 1. derivative of

    asked by Herosugar on September 26, 2012
  5. Calculus - derivatives

    Okay, I want to find the derivative of (x^x)^(x^x)... Well, I already went through the process of finding the derivative of just x^x (I used ln to do this). This is what I found... dy/dx = x^x(lnx+1) So now I want to find the

    asked by Lucy X on November 29, 2009
  6. L'Hopital's rule

    Find lim x->1+ of [(1/(x-1))-(1/lnx)]. Here is my work... =(lnx-(x-1)) / ((x-1)(lnx)) =(lnx-1) / (lnx+ (x+1)/x) This becomes(1/x) / ((1/x)+(1/x^2)) which becomes 1/ (1/x^2) This equals 1/2. I understand the answer has to be -1/2,

    asked by Anonymous on October 18, 2011
  7. math

    How do I find the derivative of ⌠lnx ⌡π cos(e^(t))dt The question above is asking for the derivative of the integral cos(e^(t)) from pi to lnx

    asked by Jen on November 12, 2013
  8. calculus

    sorry to ask a second question so soon, but i'm just not getting this one. if f(x)= 3x lnx, then f'(x)=? i used f'(x)=3x(D lnx) + D (3x) (lnx) f'(x)=3x (1/x) + 3 (lnx) so... f'(x)=3+3lnx or 3(1+lnx). unfortunately that isn't one

    asked by ken on March 2, 2013
  9. calc

    How do you find the derivative of: ln(3x^2 + x - 1) I know the derivative of lnx is 1/x

    asked by Ted on April 20, 2010
  10. calc

    find the derivative of x-lnx

    asked by jackie on November 22, 2009

More Similar Questions